2010
DOI: 10.1097/aog.0b013e3181e42220
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Documentation Using an Electronic Checklist for Shoulder Dystocia Deliveries

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Substantial rates of under-documentation by medical students were already shown by Szauter et al and Worzala et al for the context of post-encounter notes, possibly due to forgetfulness or inaccurate decisions on what is relevant and what is not [19,20]. In accordance with the results of the present study, Deering et al showed that the use of a standard checklist as a documentation aid results in significantly improved delivery notes for shoulder dystocia [21]. …”
Section: Discussionsupporting
confidence: 90%
“…Substantial rates of under-documentation by medical students were already shown by Szauter et al and Worzala et al for the context of post-encounter notes, possibly due to forgetfulness or inaccurate decisions on what is relevant and what is not [19,20]. In accordance with the results of the present study, Deering et al showed that the use of a standard checklist as a documentation aid results in significantly improved delivery notes for shoulder dystocia [21]. …”
Section: Discussionsupporting
confidence: 90%
“…Several authors have commented that these items are key components of shoulder dystocia checklists and can be helpful should litigation ensure. [11][12][13] The belief that all brachial plexus injuries result from inappropriate maneuvers at delivery has no scientific foundation. 1,2,14 In the past 10 -15 years, epidemiologic data, case studies, and computer modeling have all provided support to the theory that brachial plexus stretch and injury can result from maternal forces when the neonate's shoulder presses against the bony pelvis of the mother.…”
Section: Discussionmentioning
confidence: 99%
“…As this study evaluated only physicians-intraining, limited applicability to attending physician exists. A follow-up study by Deering et al [4] evaluated a standardized electronic checklist of key elements deemed necessary to be included in the delivery note. A total of 128 SD notes were reviewed (46 cases prior to, and 82 cases after, implementation of the checklist).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Deering et al [4] recently demonstrated that implementation of an electronic checklist improves the completeness of documentation of SD events in an Army Hospital. Additionally, studies by Deering et al [5] and Goffman et al [6], demonstrate that standardized SD drills may aid in completeness of documentation.…”
Section: Introductionmentioning
confidence: 94%